2019
DOI: 10.1097/rct.0000000000000903
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Arterial- and Venous-Phase Acquisition for Optimization of Virtual Noncontrast Images From Dual-Energy Computed Tomography Angiography

Abstract: BackgroundFollow-up with computed tomographic angiography is recommended after endovascular aneurysm repair, exposing patients to significant levels of radiation and iodine contrast medium. Dual-energy computed tomography allows virtual noncontrast (VNC) images to be reconstructed from contrast-enhanced images using a software algorithm. If the VNC images are a good-enough approximation of true noncontrast (TNC) images, a reduction in radiation dose can be ensured through omitting a TNC scan.PurposeTo compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
4
15
0
Order By: Relevance
“…We found inferior subjective image quality of VNC compared with TNC images. This is in line with the findings of Lehti et al (36), who reported higher subjective image quality of TNC compared with VNC images acquired with EID CT. Overall, in our study, the subjective image quality, image noise, and noise texture of VNC images reconstructed from arterial and portal venous phase CT were still rated as "good" by both readers.…”
Section: Discussionsupporting
confidence: 92%
“…We found inferior subjective image quality of VNC compared with TNC images. This is in line with the findings of Lehti et al (36), who reported higher subjective image quality of TNC compared with VNC images acquired with EID CT. Overall, in our study, the subjective image quality, image noise, and noise texture of VNC images reconstructed from arterial and portal venous phase CT were still rated as "good" by both readers.…”
Section: Discussionsupporting
confidence: 92%
“…Based on dual-energy information, the iodine-containing contrast material can be quantified and subtracted, resulting in a 'virtual non-contrast' (VNC) series. In theory, these could be used as a substitute for a prior 'true non-contrast' (TNC) acquisition [1,7]; in practice, however, studies reported diverging results [8][9][10][11][12][13][14]. Therefore, initial non-contrast scans are still widely performed in this clinical context [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, in a study done by Lehti et al, they have concluded that PVU images are superior than AVU images and better approximate noncontrast unenhanced (NCU) images. 21 The possible reasons could be that their study was done in second-generation, dual-source CT and they have started their arterial phase acquisition earlier compared with our scans. Complete separation of iodine signal is possible in third-generation, dual-source CT because of its advanced hardware and software applications.…”
Section: Discussionmentioning
confidence: 99%